2017
DOI: 10.5137/1019-5149.jtn.21536-17.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the levels of soluble extracellular domain of her2 protein in the sera of meningioma patients

Abstract: The results showed that serum HER2 levels were a poor biomarker for determination of pathological and prognostic characteristics of meningiomas and coupling serum HER2 levels with immuno-histo-chemistry (IHC) examination of HER2 in meningioma tissue samples would be helpful in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
2
0
3
Order By: Relevance
“…Abtahi et al demonstrated significantly higher serum levels in grade II meningioma patients compared to grade I (Abtahi et al 2019). However, in addition to the small grade II sample size (n=7) being a limitation of this study, the authors also acknowledge that other studies (Potti et al 2004) have not shown a correlation between high expression of HER2 via IHC and tumour grade or prognosis (Abtahi et al 2019).…”
Section: Blood-based Biomarkersmentioning
confidence: 86%
“…Abtahi et al demonstrated significantly higher serum levels in grade II meningioma patients compared to grade I (Abtahi et al 2019). However, in addition to the small grade II sample size (n=7) being a limitation of this study, the authors also acknowledge that other studies (Potti et al 2004) have not shown a correlation between high expression of HER2 via IHC and tumour grade or prognosis (Abtahi et al 2019).…”
Section: Blood-based Biomarkersmentioning
confidence: 86%
“…Його експресія становить від 2 до 100%. Повідомляють, що Her2 частіше визначається в доброякісних менінгіомах, а саме менінготеліальних та секреторних [17][18][19]. За даними деяких ранніх досліджень, існує обернено пропорційний зв'язок між підвищеною експресією Her2 та ступенем злоякісності пухлини, але інші джерела наявність такого зв'язку спростовують [31].…”
Section: Ukrainian Neurosurgical Journal Vol 29 N2 2023unclassified
“…Менінгіоми іншої локалізації, наприклад, мосто-мозочкового кута, розташування яких щодо внутрішньочерепних структур також значно уск ладнює хірургічне втручання, менш схильні до рецидивування/продовженого росту, ніж менінгіоми ВСС [16]. Деякі автори [17][18][19][20][21][22][23] такий агресивний к лінічний перебіг пояснюють імуногістохімічними та молекулярно-біологічними особливостями менінгіом ВСС.…”
unclassified
See 1 more Smart Citation
“…When active, this receptor binds to dimers, undergoes transphosphorylation and can transduce intracellular signals that may affect cell growth, apoptotic inhibition, migration, invasiveness, and angiogenesis, all of which can lead to tumor progression (41). Its presence is a poor prognostic factor in tumors, particularly breast carcinoma (7,42,43). Studies in the literature on this protein in meningiomas are rare (7,42), and discrepancies between the results are evident (7,40).…”
Section: Introductionmentioning
confidence: 99%